Smart Rice Box - The Prototype of Organic Rice Storage Anti-Rice Weevil for Food Security during Pandemic - Fatmawati, Uvi Desi; Pratami, Mentari Putri; Hidayat, Wahyu; Kurdianto, Kurdianto (P3M Politeknik Negeri Banjarmasin, 2023)
The need for organic rice among the people continues to increase in line with the declining level of public health due to the COVID-19 pandemic. Consuming organic rice is one way to maintain body immunity, but organic rice is susceptible to attack by Sitophilus Oryzae L, a type of rice weevil which is the main pest in postharvest commodities. Proper storage of rice is one way to address food security during a pandemic. In this study, a prototype of an anti-rice weevil (Sytophilus Oryzae L) organic rice storage was made using a Raspberry Pi controller and several additional sensors such as a camera sensor and temperature and humidity sensors. UV Hydroponic Lamp and LED Grow Light are used to reduce the growth rate of rice bugs during storage. The results showed that the whole system was running well and the rice bugs on rice were drastically reduced within 36 hours and 18 minutes of storage.